A review of feed efficiency in swine： biology and application - Patience, John F; Rossoni-Serão, Mariana C; Gutiérrez, Néstor A (Journal of animal science and biotechnology, 2015)
Feed efficiency represents the cumulative efficiency with which the pig utilizes dietary nutrients for maintenance, lean gain and lipid accretion. It is closely linked with energy metabolism, as the oxidation of carbon-containing components in the feed drive all metabolic processes. While much is known about nutrient utilization and tissue metabolism, blending these subjects into a discussion on feed efficiency has proven to be difficult. For example, while increasing dietary energy concentration will almost certainly increase feed efficiency, the correlation between dietary energy concentration and feed efficiency is surprisingly low. This is likely due to the plethora of non-dietary factors that impact feed efficiency, such as the environment and health as well as individual variation in maintenance requirements, body composition and body weight. Nonetheless, a deeper understanding of feed efficiency is critical at many levels. To individual farms, it impacts profitability. To the pork industry, it represents its competitive position against other protein sources. To food economists, it means less demand on global feed resources. There are environmental and other societal implications as well. Interestingly, feed efficiency is not always reported simply as a ratio of body weight gain to feed consumed. This review will explain why this arithmetic calculation, as simple as it initially seems, and as universally applied as it is in science and commerce, can often be misleading due to errors inherent in recording of both weight gain and feed intake. This review discusses the importance of feed efficiency, the manner in which it can be measured and reported, its basis in biology and approaches to its improvement. It concludes with a summary of findings and recommendations for future efforts.